The SYGMA programme of phase 3 trials to evaluate the efficacy and safety of budesonide/formoterol given 'as needed' in mild asthma: study protocols for two randomised controlled trials. Issue 1 (December 2017) - O'Byrne, Paul; FitzGerald, J.; Zhong, Nanshan; Bateman, Eric; Barnes, Peter; Keen, Christina; Almqvist, Gun; Pemberton, Kristine; Jorup, Carin; Ivanov, Stefan; Reddel, Helen
Abstract Background In many patients with mild asthma, the low frequency of symptoms and the episodic nature of exacerbations make adherence to regular maintenance treatment difficult. This often leads to over-reliance on short-acting β2 -agonist (SABA) reliever medication and under-treatment of the underlying inflammation, with poor control of asthma symptoms and increased risk of exacerbations. The use of budesonide/formoterol 'as needed' in response to symptoms may represent an alternative treatment option for patients with mild asthma. Methods/design The SYmbicort Given as needed in Mild Asthma (SYGMA) programme consists of two 52-week, double-blind, randomised, multicentre, parallel-group, phase 3 trials of patients aged 12 years and older with a clinical diagnosis of asthma for at least 6 months, who would qualify for treatment with regular inhaled corticosteroids (ICS). SYGMA1 aims to recruit 3750 patients who will be randomised to placebo twice daily (bid) plus as-needed budesonide/formoterol 160/4.5 μg, placebo bid plus as-needed terbutaline 0.4 mg, or budesonide 200 μg bid plus as-needed terbutaline 0.4 mg. The primary objective is to demonstrate the superiority of as-needed budesonide/formoterol over as-needed terbutaline for asthma control, as measured by well-controlled asthma weeks; a secondary objective is to establish the noninferiority of as-needed budesonide/formoterol versus maintenance budesonide plus as-needed terbutaline using the same outcome measure. SYGMA2 aims to recruit 4114 patients who will be randomised to placebo bid plus as-needed budesonide/formoterol 160/4.5 μg, or budesonide 200 μg bid plus as-needed terbutaline 0.4 mg. The primary objective is to demonstrate the noninferiority of as-needed budesonide/formoterol over budesonide bid plus as-needed terbutaline as measured by the annualised severe exacerbation rate. In both studies, use of all blinded study inhalers will be recorded electronically using Turbuhaler® Usage Monitors. Discussion Given the known risks of mild asthma, and known poor adherence with regular inhaled corticosteroids, the results of the SYGMA programme will help to determine the efficacy and safety of as-needed budesonide/formoterol therapy in mild asthma. Patient recruitment is complete, and completion of the phase 3 studies is planned in 2017. Trial registration ClinicalTrials.gov identifiers:NCT02149199 SYGMA1 andNCT02224157 SYGMA2. Registered on 16 May 2014 and 19 August 2014, respectively.